(untitled) (Research, Society and Development, 2022)
Arboviruses have been a cause of great concern and have created enormous challenges for public health in Brazil. Measures to prevent and combat Aedes Aegypt, the mosquito that transmits the virus of diseases such as Dengue, Zika and Chikungunya, are essential for the eradication of these diseases. For this, the participation and mobilization of the entire community is extremely important. In this context, the school is seen as a privileged space for the construction of knowledge and the dissemination of knowledge. This protocol will guide the development of the scope review that aims to map and describe the guidelines on prevention and control of arboviruses, addressed in health education technologies and strategies developed in the school environment, for children. It was prepared based on Joanna Briggs Institute guidelines and systematized according to the recommendations of the Preferred Reporting Items for Systematic and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR). A search for studies will be performed, using databases in the area of ​​health and education, as well as additional sources of gray literature and reference list of included studies. Publications that present guidelines on arboviruses for children in the school environment will be considered eligible. There will be no limitation as to the time, language or type of study.